2009
DOI: 10.1513/pats.200904-022rm
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Immune System and Its Relationship to the Development of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease of the lungs that usually manifests late in life. Physiologic and immunologic changes that occur in COPD often mimic changes seen in the aging lung. This has led some to characterize COPD as an ''accelerated aging phenotype.'' At the molecular level, COPD and aging share common mechanisms and are associated with significant dysregulation of the immune systems. Aging and COPD are characterized by increases in proinflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 97 publications
3
80
0
3
Order By: Relevance
“…Age-related alterations in respiratory mechanics including decreases in pulmonary elastance have previously been described in Sftpd Ϫ/Ϫ mice up to 13 wk of age (8). Our findings that lung inflammation and structural abnormalities continue to increase up to 80 wk of age are novel and in accord with reports that inflammation contributes to reduced pulmonary function (22,43).…”
Section: Discussionsupporting
confidence: 90%
“…Age-related alterations in respiratory mechanics including decreases in pulmonary elastance have previously been described in Sftpd Ϫ/Ϫ mice up to 13 wk of age (8). Our findings that lung inflammation and structural abnormalities continue to increase up to 80 wk of age are novel and in accord with reports that inflammation contributes to reduced pulmonary function (22,43).…”
Section: Discussionsupporting
confidence: 90%
“…14 Theories to explain the basis of the inflammation and other aspects of COPD such as tissue loss include accelerated ageing and autoimmunity, 15 and may vary by different COPD phenotypes that are beginning to be described.…”
Section: Copd Is Not Asthmamentioning
confidence: 99%
“…Systemic immune disturbances have been observed in patients with COPD. [17][18][19] For example, Prieto and colleagues 17 found that cytotoxic activity of peripheral blood natural killer cells and phagocytic activity of peripheral blood monocytes, macrophages and polymorphonuclear cells were significantly reduced in patients with COPD compared with healthy control patients. Systemic cell-mediated immunity has been found to be impaired in COPD and to be associated with acute respiratory tract infection among patients with COPD.…”
Section: E278mentioning
confidence: 99%
“…18 Further, recent data have shown that COPD and aging produce significant molecular similarities in immunologic alterations. 19 Immunosenescence in aging is a well-known risk factor for herpes zoster; 5 immune system changes in COPD may further render such patients more vulnerable to varicella-zoster virus reactivation than age-matched control patients. We found that risk for herpes zoster was increased among patients with COPD in all age groups.…”
Section: E278mentioning
confidence: 99%